Hubungan keuangan pusat-daerah, reformasi perpajakan dan kemandirian pembiayaan pembangunan daerah - Jaka Sriyana (Economic Journal of Emerging Markets, 1999)
Decentralisation has become as a new paradigm in the development policy and administration since 1970s. The growing interest of centralised planning is emphasised to the growth policy, and the realization that uneasily development must be controlled from the centre.